Rational design of materials with extreme negative compressibility: selective soft-mode frustration in KMn[Ag(CN)2]3 - Cairns, A; Thompson, A; Tucker, M; Haines, J; Goodwin, A (American Chemical Society, 2012)
We show that KMn[Ag(CN)₂]₃ exhibits the strongest negative linear compressibility (NLC) effect over the largest pressure range yet observed. Variable pressure neutron powder diffraction measurements reveal that its crystal lattice expands along the c axis of its trigonal cell under increasing hydrostatic pressure, while contracting along the a axis. This corresponds to a “wine-rack”-like mechanism for NLC that we find also results in anisotropic negative thermal expansion (NTE) in the same material. Inclusion of extra-framework K⁺ counterions has minimal effect on framework flexibility (and hence the magnitude of NTE/NLC) but selectively frustrates the soft phonon modes responsible for destroying NLC in the related material Ag₃[Co(CN)₆].